MANAGEMENT OF PRESCHOOL LEARNING IN DEVELOPMENT SPEAKING SKILLS AUD IN RA JEMBER DISTRICT - Pratiwi, Ratri Kurnia (International Conference on Humanity Education and Society (ICHES), 2024)
Early Childhood Education is the most influential education because this period is a determining period for the future, which is largely determined by the stimulus response received by early childhood. This period is the right time to provide encouragement as an effort to develop various aspects of children's development optimally. One aspect of development that is very important for children is language. Because through language children can express their hopes, thoughts and desires and are able to socialize with their environment. Language learning includes learning to speak, listen, write and read. This research discusses the management of early childhood language learning in RA Jember Regency, namely RA Al-Barokah An-Nur Ajung Jember. Learning management in this research includes planning learning innovations, implementing and evaluating learning innovations. Because basically management itself is carrying out management functions to manage existing resources in the hope of achieving goals effectively and efficiently. This research uses a qualitative approach with a case study type of research. The data collection techniques are interviews, observation and documentation. The data analysis used was Miles and Huberman data analysis. The results of this research are language learning innovation planning at RA Al-Barokah An-Nur Ajung Jember, which consists of planning learning tools, planning teacher quality, and planning language aspects (speaking skills). The implementation of learning innovation at RA Al-Barokah An-Nur Ajung Jember consists of four stages, namely opening, core,recalling,closing. Implementation of learning innovations in early childhood language development using methodsinteractive storytelling. Meanwhile, the evaluation of learning innovations used is formative evaluation and summative evaluation.